HOMOGENEOUS CATALYSTS FOR THE PRODUCTION OF BIODIESEL FROM GROUNDNUT OIL - AHMAD, HAFIZ; AMINU MUSA, ABUBAKAR; Ibrahim Adam, Khadija (FUDMA Journal of Sciences, 2025)
Biodiesel production from renewable feedstocks has gained significant attention as a sustainable alternative to fossil diesel due to rising energy demand and environmental concerns. In this study, biodiesel was produced from groundnut oil via alkali catalyzed transesterification using potassium hydroxide (KOH) as a homogeneous catalyst. The effects of key reaction parameters reaction temperature (50–80 °C), catalyst concentration (0.2–0.8 mol dm⁻³), reaction time (40–70 min), and methanol to oil molar ratio (5:1–11:1) on fatty acid methyl ester (FAME) yield were systematically investigated. The physicochemical properties of the groundnut oil, including acid value and moisture content, were also determined to assess its suitability for biodiesel production. The results showed that biodiesel yield increased with increasing reaction temperature and time up to optimal values, beyond which a decline in conversion was observed. Maximum FAME conversion of 94.7% was achieved at a reaction temperature of 70 °C, catalyst concentration of 0.6 mol dm⁻³, reaction time of 70 min, and methanol to oil ratio of 7:1. The findings demonstrate that groundnut oil is a viable feedstock for biodiesel production using homogeneous catalysis and compare favorably with yields reported in related studies employing both homogeneous and heterogeneous catalysts.
Keywords: Biodiesel; Groundnut Oil; Catalyst; Petroleum; FAME